High-capacity spatial-division multiplexing with orbital angular momentum based on multi-ring fiber. (28th March 2019) - Deng, Duo; Li, Yan; Zhao, Hua; Han, Yanhua; Ye, Jingfu; Qu, Shiliang
Abstract: We present a simple method of spatial-division multiplexing/demultiplexing with orbital angular momentum (OAM) based on a multi-ring optical fiber. Multi-ring fibers are ideal spatial division multiplexing carriers, providing more communication channels including orthogonal OAM multiplexing channels and spatial channels. We propose an OAM encoding scheme using multiplexing perfect vortex array (MPVA) to make full use of these channels and achieve high-capacity data communication links. For improving the coupling efficiency, perfect vortices whose radii independent of topological charge are employed to generate the intensity rings in each ring core region. Furthermore, a practical encoding scheme of multiplexing OAM is proposed to optimize the use of available OAM states. The encoded information in one core could reach L bits as there are L available OAM states in the fiber. To decode the multiplexing perfect vortex, an additional correction phase is employed to transform the perfect vortex into conventional optical vortex. By detecting the states of multiplexing OAM of each spot in this array with a perfect vortex detection phase plate, information encoded by perfect vortices is decoded. The efficient data encoding and decoding method with MPVA could be expanded to almost all kinds of multi-ring fibers to achieve high coupling efficiency and high-capacity data transmission.